The effects of feeding different levels of dicalcium phosphate to heifers on bluestem pasture - Drake, C.L.; Smith, E.F.; Spies, H.G.; Richardson, D.; Good, D.L. (Kansas Agricultural Experiment Station, 2011)
This trial was designed to study effects of low to high levels of calcium and phopphorus supplements on heifers grazing bluestem pasture. February 18, 1961, 40 Hereford heifer calves, weighing about 400 pounds each, were randomly divided into four groups and turned into a 140-acre pasture. Each morning the heifers were gathered, divided into four lots and fed the experimental rations shown in Table 49. The chemical analysis is presented in Table 48.
Keywords: Beef; Dicalcium phosphate; Bluestem pasture; Performance